2022
DOI: 10.3390/ijms23084133
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Thyroid Hormone Reduces Voltage-Gated Na+ Currents as Well as Expression of Na+/K+-ATPase in the Mouse Hippocampus

Abstract: Mice lacking functional thyroid follicular cells, Pax8−/− mice, die early postnatally, making them suitable models for extreme hypothyroidism. We have previously obtained evidence in postnatal rat neurons, that a down-regulation of Na+-current density could explain the reduced excitability of the nervous system in hypothyroidism. If such a mechanism underlies the development of coma and death in severe hypothyroidism, Pax8−/− mice should show deficits in the expression of Na+ currents and potentially also in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…The elucidation of the mechanism by which THs influence susceptibility to seizures in the brain remains necessary. It has been confirmed that elevated levels of THs can modify the function of sodium-potassium adenosine triphosphatase, thereby leading to changes in neuronal sodium concentrations, 11 ultimately resulting in a reduction of the seizure threshold. In contrast, the administration of TRH directly into the hippocampus demonstrated anticonvulsant properties in rats with amygdala-kindled seizures, as evidenced by a reduction in after-discharge duration and seizure duration.…”
Section: Putative Mechanism Of Thyroid Hormone In Epilepsymentioning
confidence: 98%
“…The elucidation of the mechanism by which THs influence susceptibility to seizures in the brain remains necessary. It has been confirmed that elevated levels of THs can modify the function of sodium-potassium adenosine triphosphatase, thereby leading to changes in neuronal sodium concentrations, 11 ultimately resulting in a reduction of the seizure threshold. In contrast, the administration of TRH directly into the hippocampus demonstrated anticonvulsant properties in rats with amygdala-kindled seizures, as evidenced by a reduction in after-discharge duration and seizure duration.…”
Section: Putative Mechanism Of Thyroid Hormone In Epilepsymentioning
confidence: 98%